APLIKASI PENGGUNAAN MESIN PEMISAH AMPAS DAN FILTRAT KACANG KEDELAI UNTUK PRODUKSI TAHU DI KECAMATAN TALANG KELAPA BANYUASIN SUMATERA -SELATAN - Muhammad Rasid; Mardiana Mardiana; Choiruddin Choiruddin (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Tofu is one of the processed soybean products that have a fairly broad market segment. Theprocess of making tofu is very simple and easy so it is mostly done by small industries and homeindustries. The process of making tofu on a household scale is generally still carried out in thetraditional way, especially in the screening process. Filtering is a process that is quite crucialin making tofu because it will involve the taste, and the quantity and quality of the tofu produced.The main problem in the small industry of PKM partners makes the production and marketingprocess of tofu products which requires a long time and energy, because the filter and pressesused are still conventional. The purpose of the PKM activity to be achieved from the productionside is by applying a soybean pulp and filtrate separator machine that can be operated moreeffectively and efficiently. From the marketing management side, namely by providing simplemanagement training that can be applied to partners and from the marketing side, namely bypromoting to the mass media, banners and improving the packaging system for tofu products.Specific targets to be achieved; the existence of a soybean grinding machine that separates pulpand juice, so that the product results are more hygienic, pay more attention to tofu processingtechnology for food safety, business management and marketing. The application of the pulpand peanut filtrate separator machine, it helps partners not to be hampered in the productionprocess. Through PKM activities, partners obtain a soybean grinding machine that canseparate the pulp and filtrate (cider). With promotions in mass media, through banners andproduct packaging systems that are more attractive, products become durable. Increasing theproductivity of partner small industries is expected to increase partner income and businessdevelopment in the future.